The Associations Between Sexual Victimization and Health Outcomes Among LGBQA College Students: Examining the Moderating Role of Social Support - DeLaney, Eryn N. (Journal of interpersonal violence, 2022)
Prior studies have demonstrated that sexual minority college students are two to four times more likely to experience sexual victimization (e.g., sexual assault and/or unwanted or uncomfortable sexual experiences) compared to their heterosexual counterparts. However, research that has focused on the detrimental effects of sexual victimization on health outcomes has paid more attention to heterosexual college samples and community-based adults. Understanding how sexual victimization influences mental health and substance use outcomes among lesbian, gay, bisexual, queer, and asexual (LGBQA) emerging adults in college is warranted given that this developmental period represents a critical risk period for trauma exposure, risk behavior, and psychological distress. Thus, the current study tested how sexual victimization was associated with depressive symptoms, post-traumatic stress disorder (PTSD) symptoms, and alcohol use disorder (AUD) symptoms among 234 diverse college students who self-identified as LGBQA. Additionally, social support was tested as a moderator. Findings indicated that sexual victimization was related to greater depressive symptoms, PTSD symptoms, and AUD symptoms. In addition, perceived social support moderated the relation between sexual victimization and depressive symptoms, however, in a direction contrary to hypotheses. In particular, higher sexual victimization was associated with greater depressive symptoms among LGBQA students with higher levels of social support (b = .29, p = .00), and was not significant among LGBQA students with lower levels of social support (b = .13, p = .26). The current study highlights the need to consider the detrimental effects of sexual victimization on health outcomes among LGBQA college students, as well as the mechanisms through which social support may be influencing these relations.